Prevalence of gastrointestinal, cardiovascular, autonomic and allergic manifestations in hospitalized patients with Ehlers-Danlos syndrome: a case-control study. (7th January 2021) - Brooks, Rachel S; Grady, James; Lowder, Thomas W; Blitshteyn, Svetlana
Abstract: Objective: Previous observations suggest an association between Ehlers-Danlos syndrome (EDS) and gastrointestinal (GI), cardiovascular, immune, and autonomic nervous system dysfunction. We sought to determine whether a hospital diagnosis of EDS is associated with a higher prevalence of these manifestations vs hospitalized patients without EDS. We also evaluated hospital outcomes. Methods: A total of 6, 021 cases and matched controls were acquired from the 2016 National Inpatient Sample. In total, 2, 007 EDS patients were identified via ICD-10 code. After bivariate analyses, multivariate logistic regression models were used to adjust for potential confounders. Results: GI conditions were found in 44% of EDS patients vs 18% of controls [odds ratio (OR) = 3.57, 95% CI: 3.17, 4.02, P < 0.0001], with irritable bowel syndrome, gastroparesis and coeliac disease strongly associated with EDS. Autonomic dysfunction, including postural orthostatic tachycardia syndrome (POTS), neurocardiogenic syncope and orthostatic hypotension was found in 20% of EDS patients vs 6% of controls (OR = 4.45, 95% CI: 3.71, 5.32, P < 0.0001). EDS patients were more likely to have food allergy (OR = 3.88, 95% CI: 2.65, 5.66, P <  0.0001) and cardiovascular complications such as mitral valve disorders, aortic aneurysm and dysrhythmias (OR = 6.16, 95% CI: 4.60, 8.23, P <  0.0001). These conditions remained highly associated with EDS after considering confounders. EDS patients were 76% more likely to have longer than average hospitalizations (OR = 1.76, 95% CI: 1.54, 2.02, P <  0.0001). Conclusion: GI, cardiovascular, autonomic and allergic manifestations are significantly more prevalent in EDS patients compared with hospitalized patients without EDS. Physicians should consider EDS in patients with unexplained GI, cardiovascular, autonomic and allergic conditions and exercise precautions when treating EDS patients in a hospital setting.